Validation of COOLOD-N2 Code Through Benchmark Calculations of IEA-R1 Reactor - Badrun, N. H.; Altaf, M. H.; H. Khan, M. J. (The Nucleus, 2015)
IEA-R1 reactor core has been modeled in COOLOD-N2 code with the aim to validate and verify the code against the experiment data provided by International Atomic Energy Agency (IAEA) through coordinated research project (CRP). Fuel cladding temperatures at different locations of an instrumental fuel assembly (IFA) at different operating powers have been calculated under steady state condition by using the COOLOD-N2 code. The calculated temperatures are then verified against the temperatures recorded by thermo couples placed for those locations of IFA in 243 configuration of IEA-R1 reactor. Reasonable agreement has been found between the calculation and experiment for fuel clad temperature which in turn implies the validity of COOLOD-N2 code in the calculation of core thermal hydraulic parameters of research reactors under steady state condition.